Knowledge and attitude regarding menstruation among adolescent boys in an urban and a rural school. - Kutu,Binita (2018)
ABSTRACT: In patriarchal societies, mostly male members‟ dominate important decisions, customs and rituals followed within families and throughout the societies. Among rituals, menstruation related beliefs are also influenced by male members. The awareness to the male is equally important in order to maintain menstrual hygiene. Thus, this study was carried out to find out knowledge and attitude of adolescent boys regarding menstruation with the aim to overcome menstrual stigma and enable girls to deal with their menstrual periods. The study was carried out in Mangala Secondary School, Myagdi and Padmodaya Secondary School, Kathmandu. Total of 151adolescents male students were taken using simple random sampling method. The semi structured questionnaires were used. The obtained data were analyzed using appropriate statistical tool. More than half of the respondents (61.4% in urban and 57.4% in rural) believed that girls couldn‟t worship or go to temple during menstruation. Similarly more than half of the respondents (57.8% in urban, 57.4% in rural) said girls should use separate mats while 32.5% of respondents in urban and 42.6% in rural stated girls couldn‟t see or touch men during menstruation. Only 37.3% of respondents in urban and 45.6% in rural had adequate knowledge regarding menstruation. Likewise in urban 22.9% while in rural 42.6% had negative attitude regarding menstruation. Only in Urban there was statistically significant association between knowledge and classes of respondents (pvalue=0.02) while ethnicity with attitude regarding menstruation (p-value=0.01) at 0.05 significant level. Findings of the study suggest that nearly half of the respondents have adequate knowledge while remaining lacked it and more negative attitude was present among respondents of rural than in urban. Thus, it can be concluded that educating boys particularly from adolescence on the menstruation and challenges that girls face could help them to become more understanding and supportive. For which educational campaigns and more reproductive health concerning programs focusing menstruation as a normal physiological process and developing positive attitude should be held among adolescents.